Answered

Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Solve for x

3^(x-2)=-2^(x-1)+3


Sagot :

3(x - 2) = -2(x - 1) + 3
 3x - 6 = -2x + 1 + 3
 3x - 6 = -2x + 4
+2x        +2x     
5x - 6 = 4
     +6  +6
     5x = 10
      5      5
       x = 2
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.